TOPICAL IMMUNOMODULATORS: FROM RHINITIS TREATMENT TO COLLECTIVE PROPHYLACTICS OF ACUTE AND CHRONIC PATHOLOGY - L.S. Namazova-Baranova; T.E. Privalova; S.A. Shadrin (Вопросы современной педиатрии, 2011)
The article contains review of Russian research results dedicated to clinical efficacy and safety assessment of topical bacterial lysate, used with therapeutic and prophylactic purpose in children with different premorbid background, including children from welfare institutions. After a course of prophylactic treatment with topical lysate it was proven for certain that prevalence of acute respiratory infections during the seasonal increase of sickness rates as well as exacerbation of chronic ENT and respiratory pathology was lower. It has been shown reasonable to perform refresher courses of treatment with the medication in order to prevent nidiformation in nasopharynx. Key words: prophylaxis, acute respiratory infections, local immunity, bacterial topical lysate, children, welfare institutions, naso- and oropharynx microflora. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 32–38.)